Performance of the Millennium Development Goals (MDGs) in Nigeria and Benin (1990-2009) - Newman, Chintuwa E. (OMICS Group, 2015)
The study evaluated the performance of the Millennium Development Goals (MDGs) in Nigeria and Benin (1990- 2009). The main analytical apparatus used to answer the research questions, achieve the research objectives and test the hypotheses of the study were: percentages, ratios, t-test, means, standard deviation and difference of means. The major goals of the programme as revealed by the study include: Goal 1: Eradicate Extreme Poverty and Hunger; on this, the study found that Nigeria’s target for poverty / hunger eradication with respect to Proportion of population on belowD1 per day (%) is 21.35% (on or before 2015) but her average poverty rate as at 2009 was 56.74%. For Benin her target on this parameter is 28.70% and 51.98% (achievement rate). Goal 2: Achieve Universal Primary Education; the study found that Nigeria’s universal education target with respect to Primary completion rate, both sexes is 100% just like that of Benin but she has achieved an average of 73.30% as at 2009 while Benin has achieved 63.33% on this variable. Goal 3: Promote Gender Equality and Women Empowerment, on this the study found that, Nigeria has made more efforts in achieving the ratio of girls to boys in primary education than Benin having reached an average of 82.53% against Benin’s 64.60% (1990-2009). While Benin has made more impact in the share of women in wage employment in the non-agricultural sector as she has achieved an average of 23.50% against Nigeria’s 18.89% (1990-2009). Therefore, for Nigeria and Benin to meet the goals in 2015 despite the global financial crisis, the study recommends that there is the need to formulate and implement policies that will promote transparency and accountability; overcome institutional constraints; promote pro-poor growth; bring about structural change and enhance distributive equity.
doi:10.4172/2151-6219.1000194
Keywords: Performance; Millennium development goals; Poverty reduction; Universal education; Gender equality; Maternal mortality; Environmental sustainability; Global partnership